What Are the Drivers of Readmission for Serious Venous Thromboembolic Events after Primary Total Knee Arthroplasty? An Analysis of 862,915 Patients - Rhoads, Colin; Emara, Ahmed K.; Pumo, Thomas; Pan, Xuankang; Zhou, Guangjin; Koroukian, Siran; Krebs, Viktor E.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2022)
Venous thromboembolism (VTE) is a relatively common complication among patients undergoing primary total knee arthroplasty (TKA). This complication occurs in a spectrum of severity ranging from an incidental finding to serious readmission-requiring events. To date, the risk factors of serious VTE that require readmission have not been characterized. This study examines the patient and hospital characteristics associated with readmission for serious VTE after TKA. The National Readmission Database (NRD) from the Agency of Healthcare Research and Quality (AHRQ) was queried for patients who underwent primary TKA from January 2016-December 2018. The study population consisted of patients who were readmitted within 90 days following primary TKA with a primary diagnosis of VTE. Multivariable regression models were constructed to evaluate patient characteristics (age, sex, insurance, elective nature of procedure, hospital characteristics, discharge status, income, and comorbidities) associated with higher risk of developing readmission-requiring VTE. Readmission rates for VTE exhibited a higher incidence in patients older than 61 (compared with 40 and under), males (OR:1.08, 95%CI [1.03–1.14]), patients with nonelective procedures (OR:20.21, 95% CI [19.16–21.32]), patients at large hospitals(OR:1.17, 95% CI [1.09–1.25]), patients at private hospitals (OR:1.19, 95% CI [1.09–1.29]), and patients with non-home discharge statuses. Comorbidities of paralysis (OR:1.52, 95% CI [1.19–1.94]), neurological disorders (OR:1.12, 95% CI [1.02–1.23]), metastatic cancer (OR:1.48, 95% CI [1.01–2.17]), obesity (OR:1.11, 95% CI [1.06–1.17]), fluid and electrolyte imbalance (OR:1.28, 95% CI [1.18–1.38]), blood loss anemia (OR:1.29, 95% CI [1.02–1.64]), and iron deficiency anemia (OR:1.24, 95 % CI [1.15–1.33]) increased risk of VTE. Certain comorbidities requiring chronic anticoagulation were associated with lower risk of VTE. Insurance status and patient income did not exhibit any correlation with VTE incidence. Patient characteristics of male sex, age > 61, and baseline comorbidities (paralysis, neurological disorders, metastatic cancer, obesity, fluid and electrolyte imbalance, and blood loss/iron deficiency anemia) were at an increased risk of developing serious VTE. Patients without continued supervision at their discharge environment were at higher risk of developing serious VTE. Extra prophylaxis and special protocols may be warranted in these patients to prevent VTE complications.
Keywords: venous thromboembolism; total knee arthroplasty; readmission; risk factors; comorbidities; discharge status